Multidisciplinary Management of Blunt Pelvic Trauma - Khanna, Pavan; Phan, Ho; Hardy, Andrew Hal; Nolan, Timothy; Dong, Paul (Seminars in Interventional Radiology, 2012)
Pelvic fractures account for ∼3% of all fractures and usually occur in patients with polytrauma. Pelvic fractures usually indicate high energy transfer and a significant mechanism of injury, and they can involve massive hemorrhage. For this reason, mortality from pelvic trauma is high, ranging from 40% to 60% among patients in shock, and up to 90% in patients considered to be in extremis. Multidisciplinary approaches in the treatment of patients with pelvic fractures have resulted in improved outcomes for these complex and challenging injuries. In this article, we describe a case of a pediatric patient who suffered severe pelvic fracture with massive hemorrhage, requiring a multidisciplinary approach for control of hemorrhage and definitive repair of injuries.
Keywords: hemorrhage; pelvic fracture; angiography; embolization